2019
DOI: 10.3390/jcs3020040
|View full text |Cite
|
Sign up to set email alerts
|

Structural Performance of Polyurethane Foam-Filled Building Composite Panels: A State-Of-The-Art

Abstract: Composite panels with polyurethane (PU) foam-core and facing materials, such as gypsum, engineered wood or some composite materials, are being used as structural members in building construction. This paper reviews and summarises major research developments, and provides an updated review of references on the structural performance of foam-filled building composite panels from 1998 to 2017. The review revealed that previous studies on the structural performance of foam-filled building composite panels could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Figure 10 describes the main failure modes of sandwich structures subjected to three-point bending tests. The results of the bending tests showed that a failure of tension in the upper skin occurs in this type of sandwich specimen with honeycomb core as compression face wrinkling [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 10 describes the main failure modes of sandwich structures subjected to three-point bending tests. The results of the bending tests showed that a failure of tension in the upper skin occurs in this type of sandwich specimen with honeycomb core as compression face wrinkling [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, rigid polyurethane foam has been widely employed as an insulation material in structures, as well as in building panels and components, due to its exceptional strength and insulating capabilities [ 1 , 2 , 3 ]. Whether it is used for insulation or building construction, in addition to the functional features of rigid polyurethane foam, its strength must match the criteria of real usage in order to avoid damage and a loss of functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane foam composites have also been studied using new materials to improve their properties. Polyurethane foam reinforced with natural fibers provides structural integrity, lightness, and higher energy absorption [26], as well as an environmentally friendly alternative [27].…”
Section: Introductionmentioning
confidence: 99%